1993
DOI: 10.7326/0003-4819-119-2-199307150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Physician Attitudes and Practice in Cancer Pain Management: A Survey From the Eastern Cooperative Oncology Group

Abstract: Professional education needs to focus on the proper assessment of pain, focus on the management of side effects, and focus on the use of adjuvant medications. A better understanding of the pharmacology of opioid analgesics is also needed. Physicians also need to educate patients to report pain and to effectively use the medications that are prescribed for pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
379
2
15

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 744 publications
(413 citation statements)
references
References 0 publications
17
379
2
15
Order By: Relevance
“…The problems encountered at this subject can be summarized as insufficient knowledge and experience of healthcare professionals in relation to pain assessment and treatment, and as their being indifferent to patient's pain (Van den Beuken-van Everdingen et al, 2007;Oldenmenger et al, 2009). It has been reported that 57 to 76% of medical oncologists do not inquire about patient's pain, and in another study it has been shown that 55% of patients try to retain his/her pain on the agenda by constantly reminding their doctors their pain (Von Roenn et al, 1993;Breivik et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The problems encountered at this subject can be summarized as insufficient knowledge and experience of healthcare professionals in relation to pain assessment and treatment, and as their being indifferent to patient's pain (Van den Beuken-van Everdingen et al, 2007;Oldenmenger et al, 2009). It has been reported that 57 to 76% of medical oncologists do not inquire about patient's pain, and in another study it has been shown that 55% of patients try to retain his/her pain on the agenda by constantly reminding their doctors their pain (Von Roenn et al, 1993;Breivik et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In particular, patients' and physicians' denial of pain have been previously identified as possible causes for pain to go untreated. 18,23 With the example of diabetic neuropathic pain, symptoms tend to develop more slowly than peripheral nerve deterioration 24 and this insidious progression may make patients more likely to accept pain as part of their chronic illness. Also, this study group represents older patients (especially those with postherpetic neuralgia) who have been observed to complain less about existing pain.…”
Section: Pain Treatment Features and Patient Attitudesmentioning
confidence: 99%
“…76 Single fraction radiation is recommended over multiple-fraction regimens for the treatment of metastatic bone pain. 77 Tere is no diference in the duration of or time to pain relief between single large fraction radiation and conventional radiation treatments involving mul- 86 tiple fractions; however, there is a higher retreatment rate in single fraction radiation. 78 Patients should also be aware of a possible transient increase in pain at the treatment site, which may be decreased with NSAIDs or corticosteroids.…”
Section: Reviewmentioning
confidence: 99%
“…A study that surveyed physicians found that 76% of physicians identifed poor pain assessment as the single most important barrier to adequate pain management. 20 An efective cancer pain assessment identifes underlying pain syndromes and mechanisms to develop the most efective treatment plan for pain control. An efective pain assessment is predicated on a trusting physicianpatient relationship and includes a detailed medical and pain history, physical exam, psychosocial and spiritual evaluation, and screen for substance abuse.…”
Section: Assessmentmentioning
confidence: 99%